Ion-precursor and ion-dose dependent anti-galvanic reduction1. Issue 59 (28th July 2015) - Tian, Shubo; Yao, Chuanhao; Liao, Lingwen; Xia, Nan; Wu, Zhikun
<x xml:space="preserve">Abstract</x> Novel strategies to tune the composition, structure and properties of nanoparticles were achieved by varying the ion-precursor and ion-dose in anti-galvanic reduction.